Shelf-life Estimation of Dried Chili in Vacuum Packaging - Ranawati, Nanda Wisha; Ahmad, Usman; Wulandani, Dyah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
This research aimed to build a model for estimating the shelf life of dried chilies in vacuum packaging stored at any storage temperature. The shelf-life estimation of dried red chilies was carried out based on the change rate of dried chilies quality parameters using the ASLT (Accelerated Shelf-Life Testing) method with the Arrhenius approach. The shelf-life estimation using the ASLT method was carried out by conditioning the storage room, which could accelerate the degradation reaction, stored at temperatures above room temperature. Prior to storage, red chilies were dried until their moisture content reaches 10%. Then it was packaged in vacuum packaging made of PE (polyethylene) plastic and stored at 35°C. During the storage period, the observation was conducted on some quality parameters, namely moisture content, color, and vitamin C content. The same experiments were also carried out at 40°C, 45°C, and 50°C to obtain different rate constant values. The shelf-life estimation results from the Arrhenius equation model were selected based on the critical parameter, in this study the critical parameter was the decrease of vitamin C content. The shelf life of dried red chilies that were packed in vacuum stored at room temperature (25°C) could maintain its quality up to 365 days. Keywords:  Arrhenius,  ASLT,  Red chili,  Vacuum packaging,  Shelf life,